Gestión de la Continuidad de Negocio: Caso Ravmar Freight del Sector Logístico - Cano Sotomayor, Eleyn (2021)
The COVID-19 pandemic demonstrated the need for the implementation of a business continuity system in organizations to deal with critical situations and events that could stop their operations. The objective of this study is to design the business continuity management system (BCMS) of the Ravmar freight agency, based on the ISO 22301:2019 standard. The work method is analytical-descriptive and applied management. To do this, virtual interviews were held with Ravmar's Senior Management to learn about its processes in detail and, then, all the information obtained was analyzed in order to determine the company's level of compliance with the requirements of the ISO standard. After the diagnosis, the proposal for the design of the BCMS was developed for the organization in question, ensuring a level of 100 % compliance of the requirements indicated by the clauses of the rule. Finally, the feasibility analysis of the design implementation was carried out, concluding that the proposal is viable and that the level of compliance presented by the Ravmar BCMS, in accordance with the requirements stipulated in ISO 22301:2019, is of 10 %. This percentage shows that the organization does not have information related to business continuity for the processes that are part of the export service.